2010
DOI: 10.1007/s10620-010-1218-1
|View full text |Cite
|
Sign up to set email alerts
|

The Case for Endoscopic Treatment of Non-dysplastic and Low-Grade Dysplastic Barrett’s Esophagus

Abstract: Non-dysplastic mucosa (ND-) in Barrett's esophagus (BE) shows clonal molecular aberrations, loss of cell cycle control, and other features of "neoplasia." These changes occur prior to morphologic expression of neoplasia (dysplasia). Morphologic evaluation of dysplasia is fraught with error, and, as a result, often leads to false-negative and false-positive diagnoses. Early "crypt dysplasia" is difficult to detect, and is often missed in routine biopsy specimens. Some studies show substantial progression rates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
42
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(43 citation statements)
references
References 104 publications
0
42
0
1
Order By: Relevance
“…Nevertheless, the impact of this development paradigm in the evolution of RFA is obvious, and both the investigators and the manufacturer of the RFA device are to be congratulated on their achievements. However, in a special article in this issue of Digestive Diseases and Sciences, Fleischer and colleagues [6] make an impassioned plea for the widespread application of RFA to all patients with Barrett's esophagus regardless of the grade of dysplasia that is premature based on the available data. Let's take a careful look at the facts, with an emphasis on the application of RFA in patients with nondysplastic Barrett's esophagus.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, the impact of this development paradigm in the evolution of RFA is obvious, and both the investigators and the manufacturer of the RFA device are to be congratulated on their achievements. However, in a special article in this issue of Digestive Diseases and Sciences, Fleischer and colleagues [6] make an impassioned plea for the widespread application of RFA to all patients with Barrett's esophagus regardless of the grade of dysplasia that is premature based on the available data. Let's take a careful look at the facts, with an emphasis on the application of RFA in patients with nondysplastic Barrett's esophagus.…”
mentioning
confidence: 99%
“…In fact, I would make the case that RFA of nondysplastic Barrett's esophagus is akin to performing plastic surgery on the esophagus; we can make it look pretty, but does RFA really change anything for the patient? Since Fleischer et al [6] tout RFA as a cancer-prevention method, I would like to use the endpoint of development of cancer to make the case that RFA in nondysplastic Barrett's esophagus is not ready for ''prime time'' for a number of reasons.…”
mentioning
confidence: 99%
“…Some authorities have suggested that all patients with BO irrespective of the presence of dysplasia should be treated with RFA [Fleischer et al 2010]. This may be related to the availability of endoscopic therapeutic options, the high cost of surveillance and the difficulty in identifying the high-risk progressors to OA.…”
Section: Non-dysplastic Barrett's Oesophagusmentioning
confidence: 99%
“…The reasons include poor interobserver correlation (reactive changes due to oesophagitis versus LGD), biopsy sampling error and regression of LGD as a result of immunosurveillance [Sharma et al 2004[Sharma et al , 2006bRajendra and Robertson, 2010]. Some authorities have estimated the incidence of OA in LGD to be between 1.7% and 14.6% per annum [Fleischer et al 2010] based on meta-analysis [Wani et al 2009] and individual studies [Skacel et al 2000;Gatenby et al 2009;Lim et al 2007;Veith, 2007]. Nevertheless, in a large multicentre study conducted by one of the authors (PS) revealed that the incidence of OA among patients with Barrett's LGD was even lower at 0.6% per year [Sharma et al 2006b].…”
Section: Introductionmentioning
confidence: 99%
“…A recent meta-analysis demonstrated that ablation significantly reduces the risk for cancer in patients with non-dysplastic BE and LGD [50] . Fleischer et al [51] proposed RFA as a safe, efficient and cost-effective method that should be considered in the management of patients with non-dysplastic or low-grade dysplastic BE, because it achieves complete response in all patients, eliminates all risk of developing cancer, with rare advent effects and less expense than surveillance in terms of absolute costs [51] . These authors reported complete response by intestinal metaplasia in 92% at 5-year follow-up.…”
Section: Endoscopic Eradication Therapymentioning
confidence: 99%